Home Cooking National Cuisine: How Jewish-Israeli Middle-Class Women Savour Home - Ore, Hadas (Cuizine, 2015)
This study uses the lens of Jewish-Israeli middle-class women’s home cooking and nostalgia to account for the reformulation of Israel’s national cuisine over three generations. My historic analysis incorporates two recent developments in the social theory of nostalgia, which argue that women negotiate gendered power relations in the family through this complex emotion, and also critique their national home. The analysis illustrates how the Zionist ideology employed nostalgia and the food arena to constitute gendered myths during the first phase, from the pre state 1920s to the 1960s (post state). These myths served the “double colonisation” of the Jewish-Arab and Arab populations by the Ashkenazi elite. The analysis also regards the societal responses to second-wave feminism in the food arena during the second phase, post 1960s. My focus on the nostalgia and home cooking of middle-class women throughout the analysis shows their dishes are enactment of ethnic diversity. Yet beyond this point, my focus illustrates that women’s home cooking is a manifestation of their longing to return to homelands (other than Israel). This idea indicates that women employ their dishes to negotiate kinship, ethnic and class-based relationships that reshape the national cuisine over generations. While some women may contest the national Zionist hierarchy through nostalgic cooking, above all, their home cooked dishes depict struggles to constitute collective belonging. Examining women’s metaphoric journey home through their cooking should, therefore, serve future comparative analysis that looks into the reformation of national cuisines in other post-colonial societies.